Development of Critical Thinking Skills in History - Ojha, Seema Shukla (JOURNAL OF INDIAN EDUCATION, 2018)
History is a written record of human experiences across time and space. The learners of history need to relate various kind of available sources to understand historical events and concepts. It is however observed that the classroom teaching in history is blended with a collection of facts, rote memorisation leading to boredom, leaving very little space for critical thinking among students. It is pertinent for teachers to evolve effective ways of learning history to generate and retain interest in the subject. How we can make the teaching-learning of history effective in schools, is a question frequently asked in different forums. This paper is the outcome of an educational intervention, with an objective to explore the effectiveness of integrating student-centred measures in a social science classroom at the elementary stage as a medium to enhance critical thinking skills and student engagement.